Comparison of Three Sequential Extraction Methods for the Determination of Iron, Manganese, and Thallium in Asphaltite Samples - Bilgin, Öykü; Fidan, Celal; Aydın, Işıl; Aydın, Fırat (ATOMIC SPECTROSCOPY PRESS LTD, 2020)
Asphaltite, which is based on petroleum, contains many elements that exist in different forms. In this study, the BCR sequential extraction (BCRSE), Tessier sequential extraction (TSE) and Stover sequential extraction (SSE) procedures were applied for the determination of Fe, Mn and Tl in different forms (exchangeable, carbonates, bound to organic and sulfide, and residual content) in the structure of asphaltite. The statistical relations between the metal values of the three different methods were determined and recommendations are given for the enrichment of these economically valuable elements from asphaltite samples. The most abundant form of Fe (%), Mn (mg kg(-1)) and Tl (mg kg(-1)) follows the order: reducible (2.28), residual (75.85) and residual (81.99) with BCRSE method; carbonates (2.46), residual (79.21) and residual (79.75) with TSE method; carbonates (2.36), residual (67.34) and residual (46.93) with SSE method. The Fe, Mn and Tl speciation scheme gives quantitative knowledge of toxicity, bioavailability, mobility, leachability and bioaccumulation, etc., for asphaltite. A comparison of the three methods shows that the TSE method is shorter and more economical, while SSE gives more detailed information about the chemical structure of the substances, and the BCRSE has reducible (as oxides) fractions for the metals. This is the first time that a comparison of the three extraction methods was carried out on asphaltites and reported. The certified reference material (CRM) NIST-1633b Coal Fly Ash was used to verify the accuracy of the method, and whether the results are in good agreement with the certified values.
Keywords: HEAVY-METALS; FRACTIONATION; SPECIATION; MOBILITY; ELEMENTS; REGIONASH